Hambatan Yang Dirasakan Perawat dalam Implementasi Pencegahan Luka Tekan - Lansa, Syamsuriah (Journal of Telenursing (JOTING), 2024)
This study aims to review the research and make traps with a scoping review approach. Literature searches were carried out using electronic engines on 5 databases, PubMed, Science Direct, Cochrane, Wiley, and Google Scholar with a time limit of 2010 - 2023 and full text. Of the 9,768 articles, 6 articles were obtained that fit the research objectives. After analysis, 5 themes were identified, high workload, lack of knowledge and skills, linsufficient resources, unstable patient condition and low priority. Pressure injuries in the ICU can be prevented by reducing perceived barrier nurse toward pressure injury. Multidisciplinary supports expected to facilitate nurses in implementing maximum pressure injuries prevention Keyword : ICU Nurse, Pressure Injury Prevention, Barrier